Entre navios, a cidade e a faina: São Francisco do Sul - SC e a atividade portuária - Wagner, Daniela Feyh (2020)
Geography, the Science that studies the relationship between society with the geographic space, is extremely broad. This broadness is justified by the quantity of phenomena that can be explained by it, being grouped in different areas that together compose what we know as Geography. Within this wide universe of elements of reality that can be explained by this science, we have the production of the geographic space by the economy. Thus, this study aims to understand how is constituted the space of São Francisco do Sul-SC, city located in the northern coastal region of Santa Catarina, observing it by its seaport activities, being that its main vector of economic development. For such were chosen three main elements that stand out in the production of space. The São Francisco do Sul Harbor, it’s history, intern and external flux, infrastructure and project of expansion; the port work, it’s relation with the syndicates and changes that came with the port modernizing laws; and the city/port relationship. Thus, for the making of this research, it was opted for the utilization of a methodology centered around two main axis: field work for systematic observations with interviews, besides reading of a vast bibliography about the port theme, labor and the port/city relationship. First of all, the intention of this study is to build geographic knowledge about São Francisco do Sul, taking a critical look of how this space is shaped by it’s port dynamic. As a result of the analyzes, the research showed that about 80% of the municipality's economy comes from port activities, as well as conflicts in the port-city relationship, which mainly translate into the intense flow of cargo vehicles and trains circulating in the urban center. In addition, port workers are responsible for handling cargo in ports and how changes in legislation have made their work relationships more precarious.